2020
DOI: 10.1159/000506440
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ Disease-Related Pancytopenia Improved after Radioactive Iodine Ablation

Abstract: Graves' disease is an autoimmune disease that affects the thyroid glands which often results in enlarged thyroid glands, and it is the most common cause of clinical hyperthyroidism especially in young patients. Radioiodine ablation is a radiation therapy in which radioactive iodine is administered to destroy or ablate thyroid cells. It is commonly used for the treatment of Graves' disease. We report on a 39-year-old male, who presented with Graves' disease, found to have pancytopenia and hypocellular bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…During the treatment of GD, the concentration of hepcidin decreases However, GD treatment results in the restoration of cell number in most cases of pancytopenia or leukopenia associated with GD. Recovery can take anywhere from a few weeks to over a year (11) .Another study indicated the role of radioiodine iodine treatment in improving complete blood count levels. The most frequent haematologic abnormalities identified at GD diagnosis according to a prior study return to normal following the start of radioiodine treatment and the distribution of white blood cells may differ in GD in contrast to other infectious disorders, including leukopenia (12) .…”
Section: Discussionmentioning
confidence: 99%
“…During the treatment of GD, the concentration of hepcidin decreases However, GD treatment results in the restoration of cell number in most cases of pancytopenia or leukopenia associated with GD. Recovery can take anywhere from a few weeks to over a year (11) .Another study indicated the role of radioiodine iodine treatment in improving complete blood count levels. The most frequent haematologic abnormalities identified at GD diagnosis according to a prior study return to normal following the start of radioiodine treatment and the distribution of white blood cells may differ in GD in contrast to other infectious disorders, including leukopenia (12) .…”
Section: Discussionmentioning
confidence: 99%
“…In infections caused by enterococci, staphylococci, and pneumococci, a gradual increase in resistance and difficulty of treatment is observed. So, Linezolid is one of the new antibiotics that has recently been introduced for clinical use with gram positive efficacy [12]. Linezolid is the first introduced antibiotic of the oxazolidinone group.…”
Section: Linezolid and Myelosuppressionmentioning
confidence: 99%
“…Irreversible Optic and Peripheral Neuropathy when Used for 28 Days or More Toxic optic neuropathies are characterized by gradual, progressive, painless, and bilaterally symmetric visual loss that affects central vision and results in a central or Centro cecal scotoma. Long-term linezolid interferes with bacterial ribosomes as well as mammalian ribosomes, impairing mitochondrial oxidative phosphorylation and protein synthesis [12].…”
Section: Lactic Acidosismentioning
confidence: 99%